RACISMO IMPLÍCITO EN “MARCELO BRITO” Y LA FAMILIA DE PASCUAL DUARTE DE CAMILO JOSÉ CELA - Mizrahi, Irene; Liashchynskaya, Viktoryia (ConSecuencias, 2024)
Abstract Using Mikhail Bakhtin's theory, this work aims to demonstrate that both the discourse of Anselmo, the narrator of the short story "Marcelo Brito," and the discourse of the anonymous speaker posing as the transcriber of the novel The Family of Pascual Duarte are monological. It argues that, in both works, Cela creates these monological discourses with the veiled purpose of parodying them: parody is the tool the author uses to denounce these monological discourses, encouraging us to unmask them. Only by doing so will we become aware of how both speakers secretly reinforce and promote racism against Afro-descendants and Gypsies, which was similarly hidden behind the toxic discourses propagated by Francisco Franco's fascist regime during the post-war period in which Cela composed these works. Resumen Empleando la teoría de Mijaíl Bajtín, este trabajo se propone demostrar que monológicos son tanto el discurso de Anselmo, el narrador del cuento “Marcelo Brito”, como el discurso del emisor anónimo que se hace pasar por el transcriptor de la novela La familia de Pascual Duarte. Se defiende que, en ambas obras, Cela crea estos discursos monológicos con el velado propósito de parodiarlos: la parodia es el recurso que el autor emplea para denunciar estos discursos monológicos, estimulándonos a desenmascararlos, pues solo así cobraremos conciencia de cómo ambos emisores a escondidas refuerzan y promocionan el racismo contra los afrodescendientes y los gitanos que igualmente se ocultaba tras los tóxicos discursos que el régimen fascista de Francisco Franco propagaba durante la época de posguerra en la que Cela compuso las obras.